Perceptions, Knowledge and Practice of Self-Medication among Undergraduate Pharmacy Students in Malaysia: A Cross Sectional Study - Elkalmi, Ramadan Mohamed; Elnaem, Mohamed Hassan; Rayes, Ibrahim Khalid; Alkodmani, Ramez Mohamed; Elsayed, Tarek Mohamed; Jamshed, Shazia Qasim (Journal of Pharmacy Practice and Community Medicine)
Background: Awareness about health status has increased the prevalence of self-medication. Several factors play role in self-medication like gender, socioeconomic status, education level and frequency of illness. Objective: To explore the perceptions, knowledge and practice of self-medication among pharmacy students from International Islamic University Malaysia (IIUM), Kuantan. Methods: A cross-sectional study was conducted from October to December 2015. A convenience sample was taken from year 1 to year 4 of pharmacy students. Data was analyzed using SPSS version 21. Results: Of 462 questionnaires distributed, 379 were returned giving a response rate of (88.3%). The results show significant difference on the level of knowledge among pharmacy students from different academic levels (p< 0.001). The total mean score of knowledge about self-medication was 4.57+1.89. For perception, the vast majority of the students believed that self-medication can save time (88.8%) and money (73.7%). Sore throat, headache, fever and cold were the most common inducements complaints for self-medication 68.4%; 64.9%, 64.6%, 60.9%; respectively. Furthermore, health supplements (29.8%), antipyretics (23.9%) and analgesics (23.4%) were the commonly used medication. Almost all (90.7%) of the students believed that self-medication can be practiced when the illness is not too serious. Conclusion: The study findings depicted that the majority of study participants have insufficient knowledge about self-medication. Early exposure to knowledge about self-medicine in the early stages of undergraduate pharmacy education is imperative to ensure a proper and appropriate way to self-medication among students.
Keywords: Self-medication; pharmacy students; perception; knowledge level; Malaysia